Purification and characterization of a hydrolysis‐resistant lipase from Aspergillus terreus. (21st November 2013) - Shi, Hui; Meng, Yao; Yang, Min; Zhang, Qinglian; Meng, Yanfa
Abstract Lipase from Aspergillus terreus was purified to homogeneity using ammonium sulfate precipitation and chromatographies with Q‐Sepharose and Sephacryl S‐200. It showed a single band on SDS‐PAGE and IEF‐PAGE with a relative molecular mass of 37.2 kDa and pI of 3.2. Its glycoprotein nature was confirmed with the percentage of saccharides of 5.02% and 3.88% determined by the phenol/sulfuric acid and anthrone/ sulfuric acid methods, respectively. The lipase hydrolyzed both plant oils and animal oils, with the Km value for substrate p‐NPP of 16.42 mM at pH 6.0, 50 °C. The enzyme was tolerant in a wide range of pH (pH 3–12) with optimum activity at pH 4.0. It remained stable under the highest temperature of 65 °C, with maximal activity at 50 °C. Ca2+, Co2+, Mn2+, and Ni2+ stimulated enzyme activity, but Hg2+ caused inhibition. Detected detergents had no obvious effect on enzyme activity, except SDS, which stimulated the activity at lower concentrations but inhibited the activity at higher concentrations. The inhibitory effect on enzyme activity of phenylmethanesulfonyl fluoride revealed that the Ser was involved in catalysis. Saccharides had no obvious effect on enzyme activity but could enhance its thermostability. Furthermore, the enzyme was resistant to trypsin digestion.